Safety of the use of gold nanoparticles conjugated with proinsulin peptide and administered by hollow microneedles as an immunotherapy in type 1 diabetes. Issue 1 (27th January 2022) - Tatovic, D; McAteer, M A; Barry, J; Barrientos, A; Rodríguez Terradillos, K; Perera, I; Kochba, E; Levin, Y; Dul, M; Coulman, S A; Birchall, J C; von Ruhland, C; et al.
Abstract: Antigen-specific immunotherapy is an immunomodulatory strategy for autoimmune diseases, such as type 1 diabetes, in which patients are treated with autoantigens to promote immune tolerance, stop autoimmune β-cell destruction and prevent permanent dependence on exogenous insulin. In this study, human proinsulin peptide C19-A3 (known for its positive safety profile) was conjugated to ultrasmall gold nanoparticles (GNPs), an attractive drug delivery platform due to the potential anti-inflammatory properties of gold. We hypothesised that microneedle intradermal delivery of C19-A3 GNP may improve peptide pharmacokinetics and induce tolerogenic immunomodulation and proceeded to evaluate its safety and feasibility in a first-in-human trial. Allowing for the limitation of the small number of participants, intradermal administration of C19-A3 GNP appears safe and well tolerated in participants with type 1 diabetes. The associated prolonged skin retention of C19-A3 GNP after intradermal administration offers a number of possibilities to enhance its tolerogenic potential, which should be explored in future studies Graphical Abstract: